Current Topics in Biochemical Engineering - Shiomi, Naofumi (IntechOpen, 2019)
Genetic and cellular technologies in life science have recently achieved remarkable progress, and thus the roles of biochemical engineers have also been changed to incorporate the use of new technology. Therefore, this book deals with current topics in biochemical engineering. The chapters of this book discuss research that has introduced artificial enzymes, kinetic models in bioprocessing, a small-scale production process, and production of energy with microbial fuel. These chapters offer novel ideas for the production of effective compounds and energy. Moreover, other research has introduced the production technology of stem cells and biomedical processes using nanoshells and extracellular vesicles. These chapters will provide novel ideas to produce effective compounds and develop therapies for various diseases.